The Effects of Feeding Strategies on Performance and Liver Abscess Prevalence on Growing Beef × Dairy Steers - W. Cole Ellis (Kansas Agricultural Experiment Station Research Reports, 2026)
Objective: The objectives of this study were to evaluate the effects of diet, intake and use of tylosin phosphate on growth performance and liver abscess prevalence on growing beef × dairy steers. Study Description: A total of 529 beef × dairy crossbred steers were used in a 126-day backgrounding study. Pens were randomly assigned to one of five treatments: a 50 net energy for gain (NEg) diet targeting 2 lb of gain/day (50-2 lb), 60 NEg diet targeting 2 or 3 lb of gain/day (60-2 lb and 60-3 lb, respectively), or a 64 NEg diet fed for ad libitum intake with or without tylosin phosphate (64-ALT and 64-ALNT, respectively; Tylovet 100, Huvepharma, Peachtree City, GA). Steers had an ultrasound on days 0 and 126 to determine liver abscess prevalence. The Bottom Line: Feeding a 60 NEg diet targeting 3 lb of gain/day reduced LA prevalence without sacrificing efficiency when compared with a high energy ad libitum diet. Additionally, inclusion of tylosin phosphate did not reduce liver abscess prevalence in steers fed 64 NEg diets.
Keywords: crossbred; liver abscess; tylosin phosphate